Establishment of a Live-Imaging Analysis for Polarized Growth of Conchocelis in the Multicellular Red Alga Neopyropia yezoensis - Hiwatashi, Yuji; Shimada, Mizuho; Mikami, Koji; Takada, Nagisa (Frontiers in Plant Science, 2022)
A wide range of tip-growing cells in plants display polarized cell growth, which is an essential cellular process for the form and function of individual cells. Understanding of the regulatory mechanisms underlying tip growth in terrestrial plants has improved. Cellular processes involved in tip growth have also been investigated in some algae species that form filamentous cells, but their regulatory mechanisms remain unclear. In the macro red alga Neopyropia yezoensis, for which genome information has recently been released, the conchocelis apical cell exhibits tip growth and forms a filamentous structure. Here, we report a live-imaging technique using high-resolution microscopy to analyze the tip growth and cell division of N. yezoensis conchocelis. This imaging analysis addressed tip growth dynamics and cell division in conchocelis apical cells. The directionality and tip growth expansion were disrupted by the application of cytoskeletal drugs, suggesting the involvement of microtubules (MTs) and actin filaments (AFs) in these processes. A growing apical cell mostly contained a single chloroplast that moved toward the expanding part of the apical cell. Drug application also inhibited chloroplast movement, implying that the movement may be dependent on the cytoskeleton. The study determined that live-imaging analysis is a versatile approach for exploring the dynamics of tip growth and cell division in N. yezoensis conchocelis, which provides insights into the regulatory mechanisms underlying cellular growth in multicellular red algae.